Integrated effects of compost and nano foliar spray on the growth and fruit quality of sweet peppers under greenhouse conditions - Sayed, Hassan A. A.; Ali, Khaled A. M.; Abdelhamid, Mahmoud A.; Nofal, Ali S. A.; Hamad, Saleh A. S.; Lai, Qinghui; Moustafa, Mohamed Ahmed; Abd El-wahhab, Gomaa G. (Frontiers in Plant Science, 2026)
IntroductionEnhancing vegetable growth and fruit quality in greenhouse production systems through sustainable nutrient management is a key challenge in modern horticulture. Therefore, this study evaluated the effects of mechanically produced compost and nano-foliar spray application on the growth and fruit quality of sweet pepper (Capsicum annuum L.) grown in a greenhouse under sand and clay soil conditions.MethodsThe experiment was conducted in a controlled plastic greenhouse located at Al-Azhar University, Cairo, Egypt (30° 2′ 44′′ N, 31° 15′ 44′′ E), over the 2022–2023 growing season. It was conducted using a factorial design consisting of compost at five volumetric rates (0%, 10%, 15%, 20%, and 25%), two soil types (sand and clay), and nano foliar spray at three concentrations (0, 1, and 2 cm3 L–1), with three replicates per treatment. Plant growth characteristics and fruit quality parameters were measured. The data were analyzed using three-way analysis of variance, and treatment means were compared using Duncan’s multiple range test (p ≤ 0.05).ResultsThe results indicated that the level of compost, soil type, and foliar nano-spray significantly affect pepper growth and fruit quality. The treatment (20% compost in sandy soil + 2 cm3 L–1 of nano-fertilizer) showed better performance in most vegetative growth characteristics and fruit quality traits compared to the other treatments, with a yield of 72.4 tons/ha. Furthermore, Multivariate analyses, including Principal Component Analysis (PCA) and correlation analysis, highlighted strong associations between yield and physiological traits related to photosynthetic capacity and antioxidant status.DiscussionThe proposed approach highlights the integration of organic amendments and nano-based nutrient management as an effective strategy to increase productivity and produce more sustainable vegetables.